Pottery Use and Starchy Foods During the Shuangdun Culture (ca.7.3–6.8 Ka BP) in the Middle Catchment of the Huai River, China - Li, Weiya; Luo, Wuhong; Yao, Ling; Xuan, Huali; Yi, Wenwen; Tian, Weixin; Zhang, Dailing; Sun, Yajie; Kan, Xuhang; Zhang, Juzhong (Frontiers in Earth Science, 2022)
The exploitation of rice and millet has been revealed at a few archaeological sites associated with the Shuangdun Culture (ca. 7.3-6.8 ka BP) in the middle catchment of the Huai River, China. Nevertheless, how rice, millet, and other types of plant foods were consumed at other contemporaneous sites in the same region still needs supporting information from more case studies. This paper examines pottery sherds (n=21) excavated from another representative Shuangdun Culture site of Houjiazhai with starch grain analysis. Multiple types of pottery vessels provide starch remains from rice (Oryza sativa), foxtail millet (Setaria italica), broomcorn millet (Panicum miliaceum), Job’s tears (Coix lacryma-jobi), Triticeae, roots of snake gourd (Trichosanthes kirilowii), lotus root (Nelumbo nucifera), Chinese yam (Dioscorea panthainca), lily bulbs (Lilium sp.), acorns (Quercus sp.), beans (Vigna sp. or/and Vicia sp.). Further quantitative analysis of the starch data indicates that cereals, including rice and millet, were predominantly consumed in the pottery vessels. Changes and continuities of culinary practices are also present at Houjiazhai, which are reflected in the different pottery assemblages as well as the utilized plant species in different occupation phases at the site. Combining previous studies, this paper also reveals the differences and similarities of the past population in choosing their plant food resources during the period of Shuangdun Culture in the middle catchment of the Huai River, China.